Experimental investigation and 3D finite element prediction of temperature distribution during travelling heat sourced from oxyacetylene flame - Alkali, A.U. (Institute of Physics Publishing, 2015)
This paper presents a 3D transient finite element modelling of the workpiece temperature field produced during the travelling heat sourced from oxyacetylene flame. The proposed model was given in terms of preheat-only test applicable during thermally enhanced machining using the oxyacetylene flame as a heat source. The FEA model as well as the experimental test investigated the surface temperature distribution on 316L stainless steel at scanning speed of 100mm/min, 125mm/min 160mm/min, 200mm/min and 250mm/min. The parametric properties of the heat source maintained constant are; lead distance Ld =10mm, focus height Fh=7.5mm, oxygen gas pressure Poxy=15psi and acetylene gas pressure Pacty=25psi. An experimental validation of the temperature field induced on type 316L stainless steel reveal that temperature distribution increases when the travelling speed decreases. Â© Published under licence by IOP Publishing Ltd.